2017
DOI: 10.1016/j.numecd.2017.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Associations between dietary salt, potassium and blood pressure in South African adults: WHO SAGE Wave 2 Salt & Tobacco

Abstract: These preliminary results indicate that high dietary Na:K ratio may lead to a greater increase in BP and hypertension risk with age. Interventions to increase potassium intakes alongside sodium reduction initiatives may be warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 33 publications
3
26
2
2
Order By: Relevance
“…4 Penelitian yang dilakukan pada masyarakat dewasa di Afrika utara juga mendapatkan hasil yang sama dimana asupan natrium : kalium yang tinggi dalam makanan merupakan penyebab peningkatan tekanan darah dan resiko ini lebih besar terjadi dengan pertambahan usia. 5 7 Riset pada hewan coba yang dilakukan oleh nomura dkk mendapatkan hasil bahwa hewan coba yang diberikan diet tinggi garam dan rendah kalium mengalami peningkatan tekanan dara. 8 Penelitian yang dilakukan oleh Xu ji dkk di cina dengan memperoleh hasil bahwa asupan natrium yang tinggi dapat menyebabkan hipertensi, begitupun penelitian yang dilakukan Atun dkk tahun 2014 juga mendapatkan hasil bahwa asupan natrium berhubungan dengan kejadian hipertensi dimana asupan natrium yang tinggi dapat meningkatkan resiko tekanan darah tinggi (OR: 5,7) 9 Sistem kerja renin angiotensin dan aldosteron sangat berperan dalam timbulnya hipertensi.…”
Section: Abstrakunclassified
“…4 Penelitian yang dilakukan pada masyarakat dewasa di Afrika utara juga mendapatkan hasil yang sama dimana asupan natrium : kalium yang tinggi dalam makanan merupakan penyebab peningkatan tekanan darah dan resiko ini lebih besar terjadi dengan pertambahan usia. 5 7 Riset pada hewan coba yang dilakukan oleh nomura dkk mendapatkan hasil bahwa hewan coba yang diberikan diet tinggi garam dan rendah kalium mengalami peningkatan tekanan dara. 8 Penelitian yang dilakukan oleh Xu ji dkk di cina dengan memperoleh hasil bahwa asupan natrium yang tinggi dapat menyebabkan hipertensi, begitupun penelitian yang dilakukan Atun dkk tahun 2014 juga mendapatkan hasil bahwa asupan natrium berhubungan dengan kejadian hipertensi dimana asupan natrium yang tinggi dapat meningkatkan resiko tekanan darah tinggi (OR: 5,7) 9 Sistem kerja renin angiotensin dan aldosteron sangat berperan dalam timbulnya hipertensi.…”
Section: Abstrakunclassified
“…Median 24-hour Na excretion (n=874) was equivalent to a median salt intake of 6.3 g/day (range 1–43 g/day); 35% had values within the desirable range (<5 g salt/day), 37% had high values (5–9 g salt/day) and 28% had very high values (>9 g salt/day). We have previously reported that median salt intakes are higher in younger than older (50+ years) adults in this cohort (8.6 g/day vs 6.1 g/day; p<0.001), and in urban compared with rural dwellers (7.0 g/day vs 6.0 g/day; p=0.033) 38 but further analysis of Na versus iodine excretion, by demographic breakdown, is outside the scope of the current analysis. No significant difference in median UIE was found according to age category (18–49 years; 50+ years) or sex; however, median UIE was significantly higher in urban compared with rural dwellers (128 (IQR 147) vs 115 (IQR 119); p=0.041).…”
Section: Resultsmentioning
confidence: 52%
“…As well as changes to the food supply, nutrition education activities undertaken by the Department of Health and non-governmental organisations in South Africa aim to change consumer behaviour related to table salt use. 41 42 The timing of the WHO-SAGE Salt & Tobacco substudy in South Africa was planned to provide a baseline population salt intake 38 1 year before mandatory salt legislation, in order for comparison in the same cohort 1 year after introduction of the legislation 29 in SAGE Wave 3. The data reported in this paper relate to the presalt reduction legislation baseline timepoint.…”
Section: Discussionmentioning
confidence: 99%
“…In a study carried out in the capital of another Portuguese-speaking country, Maputo, Mozambique, this percentage was 96.0% [ 52 ]. In South African adults, the non-compliance with the daily potassium recommendation was 91.0% [ 53 ].…”
Section: Discussionmentioning
confidence: 99%